Expanding health care services for poor populations in developing countries: Exploring India’s RSBY national health insurance programme for low-income groups - Virk, A (2013)
Health is deemed central to a nation’s development. Accordingly, health care reform and expansion are key policy priorities in developing countries. Many such nations are now testing various methods of funding and delivering health care to local disadvantaged populations. Similarly, India launched the Rashtriya Swasthya Bima Yojana (RSBY) national health insurance programme for low-income groups in 2008. The RSBY intends preventing catastrophic health-related expenditure by improving recipients’ access to hospital-based care. This thesis is an in-depth qualitative evaluation of the RSBY in Delhi state. It examines the RSBY’s effectiveness in fulfilling its goals and meeting local health care needs. Walt and Gilson’s (1994) actors-content-process-context model informs the research design and an actor-centred “responsive” (Stake 1975) or “constructivist” approach guides data analysis. Three research questions are examined: (i). Why was a health insurance programme launched and why now? Why was this model favoured over alternate methods of service expansion? (ii). Is the RSBY delivered as intended? If not, why? (iii) How does the RSBY affect patients’ access to services? The findings are based on documentary sources, observation of implementation sites and activities and 164 semi-structured interviews with RSBY policymakers, insurers, NGOs, doctors, and patients. The results show improved access to curative and surgical care for RSBY patients. However, RSBY’s focus on hospitalisation and omission of primary and outpatient services had undesired negative effects. The lack of ambulatory facilities led RSBY patients to self-medicate or use dubious quality informal providers. By only allowing inpatient care, the RSBY also seemingly encouraged the substitution of outpatient care with costlier hospitalisations. In effect, the RSBY’s design contributed to cost increases and poor patient outcomes. While more funds and human resources were needed to improve RSBY implementation, the performance of frontline agencies could potentially improve through more stable, longer-term contracts. Similarly, modifying RSBY’s monetary incentives for doctors may lead to better service delivery by them. By evaluating the RSBY’s strong points and shortcomings, this thesis provides key lessons on strengthening policy design and health service delivery in developing countries. Thereby, it makes a broader contribution to understanding the determinants of successful policymaking.